2017
DOI: 10.1016/j.clinph.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of saccadic eye movements on the sensor-level magnetoencephalogram

Abstract: We have here characterized the MEG saccadic artifact in both the spatial and the frequency domains for saccades of different directions. This could be important in ruling in or ruling out artifact in MEG recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Saccadic eye movements generate non-neural signals, recorded by the MEG mostly in frontal sensors (Gawne et al, 2017). While ICA is commonly used as a way to remove eye-movement artifacts, we chose to keep the signal as is, as removing ICA components related to eye movements may also remove temporally associated neural activity.…”
Section: Meg Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccadic eye movements generate non-neural signals, recorded by the MEG mostly in frontal sensors (Gawne et al, 2017). While ICA is commonly used as a way to remove eye-movement artifacts, we chose to keep the signal as is, as removing ICA components related to eye movements may also remove temporally associated neural activity.…”
Section: Meg Data Preparationmentioning
confidence: 99%
“…The rotation of the eyeball and the contraction of the periocular muscles can be detected by the MEG sensors, contaminating the signal with non-neural sources (Carl et al, 2012;Gawne et al, 2017;Keren et al, 2010). In particular, the eye dipole rotation generates low frequency artifacts, strongest at sensors located fronto-laterally (Gawne et al, 2017). Inspection of the time course of the ERFs (Supplementary materials Fig.…”
Section: Control Analysesmentioning
confidence: 99%
“…It has been reported that saccadic eye movements cause noise, especially in the high-frequency bands (Gawne, Killen, Tracy, & Lahti, 2017). Therefore, it was necessary to control for saccadic eye movements during our tasks and analyses.…”
Section: Magnetoencephalography and Magnetic Resonance Imaging Datamentioning
confidence: 99%
“…First, the rotation of the eye creates a rotation of an electrical dipole located between the cornea and the retina, called the corneoretinal dipole (CRD). The CRD causes large frontal modulations of scalp EEG (Lins, Picton, Berg, & Scherg, ) and magnetoencephalogram (MEG; Gawne, Killen, Tracy, & Lahti, ; Oakley, Sullivan, Roeder, & Flynn, ). Second, saccades (mostly vertical ones) are accompanied by ballistic eyelid movements, which are manifested on the scalp very similarly to the CRD, but for a slightly longer duration (Barry & Jones, ; Plöchl, Ossandón, & König, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, saccades (mostly vertical ones) are accompanied by ballistic eyelid movements, which are manifested on the scalp very similarly to the CRD, but for a slightly longer duration (Barry & Jones, ; Plöchl, Ossandón, & König, ). Third, the recruitment of muscle units of the extraocular muscles while executing saccades produces a saccadic spike potential (SP)—a transient signal deflection that is observed in occipitoparietal EEG electrodes (Keren, Yuval‐Greenberg, & Deouell, ; Thickbroom & Mastaglia, ; Yuval‐Greenberg & Deouell, ), frontal and temporal MEG sensors (Carl, Açık, König, Engel, & Hipp, ; Gawne et al, ), and at certain regions in human intracranial recordings (Jerbi et al, ; Kovach et al, ). Fourth, and most problematic, is the visual cortical activity that is correlated with the execution of saccades (saccade‐related visual activity; SVA).…”
Section: Introductionmentioning
confidence: 99%